Biological macromolecule chitosan grafted co-polymeric composite: bio-adsorption probe on cationic dyes - Khairkar, Shyam R.; Pansare, V. Shubham; Shedge, Amol A.; Chhatre, Shraddha; Kulal, Dnyaneshwar K.; Patil, Vishwanath R.; Pansare, V. Amol (Polymer Bulletin, 2022)
Chitosan biological macromolecule is a versatile polymer; chemical modification has been carried out that lead to the formation of chitosan grafted polymers composites (Chito-g-PC). We proposed synthesis of six various Chito-g-PC as sorbents for toxic dyes. A novel graft copolymerization method based on radical polymerization with vinyl monomer like acrylic acid, acrylamide, N-isopropylacrylamide, methacrylic acid and polyacrylonitrile were utilized in order to address the large amount of swelling at four different pH buffers solution. The effect of initiator and monomer concentration, time and temperature on % grafting and % grafting efficiency were performed. Comparative characterization of Chito and Chito-g-PC were evaluated by SEM, XRD and FTIR, as well as solubility characteristics of the composites were determined by various pH buffer solution. Cationic toxic dyes Malachite green (MG) and Methylene blue (MB) were selected as the sorbet, and Chito-g-PC were used as biosorbents. Thermodynamic analysis showed that the sorption process was spontaneous and endothermic with an increased randomness. The sorption experiments were realized with six different Chito-g-PC for MG and MB at various pH.
Keywords: Acrylamide; acrylic acid; Bio sorbent; Chitosan biological macromolecule